A hierarchical Zn2Mo3O8 nanodots–porous carbon composite as a superior anode for lithium-ion batteries - Zhu, Y.; Zhong, Y.; Chen, G.; Deng, X.; Cai, R.; Li, L.; Shao, Zongping (The Royal Society of Chemistry, 2016)
A hierarchical Zn2Mo3O8 nanodots-porous carbon composite has been successfully synthesized via the ingenious combination of ion exchange and molten salt strategies, and the composite exhibits remarkable performance as an anode material for lithium-ion batteries.